The Use of Creative Movement Method in Teaching Foreign Languages to Very Young Language Learners - Sila, Anita; Lenard, Vid (European Journal of Social Science Education and Research, 2022)
The creative movement method is a holistic teaching method that enables children to develop language skills through art not just by looking and seeing, hearing and listening, speaking and talking, but also by conducting various motions and movements – experiencing while playing. Children can learn holistically only when their minds and bodies are an indivisible whole. When all their senses are engaged, children remember and recall information more effectively. The present paper describes the use of the creative movement method in teaching phonological awareness skills in a foreign language (English) to 13 Slovenian preschool children with a mean age of 5.8 years. The aim of the study was to determine children’s success rates in producing words and alliteration after being given the first sound of word (vowels /æ/, /e/, /?/, /?/, /?/) in English, both with and without movement support. Children participated in two 45-minute long teaching sessions (the second took place after two weeks). There was no additional training between each session and the test. The results of the test after two weeks from the last session show that creative movement support proved essential for children in recalling words and producing alliteration in English. The study also includes some guidelines for the method’s use in teaching foreign languages to very young language learners.
Keywords: creative movement, alliteration, foreign language, phonological awareness, preschool children.